2014
DOI: 10.1049/iet-spr.2013.0005
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive genetic algorithm‐based approach to improve the synthesis of two‐dimensional finite impulse response filters

Abstract: International audienceThe design of finite impulse response (FIR) filters can be formulated as a non-linear optimization problem reputed to be difficult for conventional approaches. The constraints are high and a large number of parameters have to be estimated, especially when dealing with 2-D FIR filters. In order to improve the performance of conventional approaches, we explore several stochastic methodologies capable of handling large spaces. We specifically propose a new genetic algorithm in which some inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 49 publications
(85 reference statements)
1
11
0
Order By: Relevance
“…All of these algorithms can make full use of the rules and information of the previous mining and conduct rule updating, which can avoid duplication work and improve work efficiency. However, in most actual production processes, the attribute values of various fields to be mined are not only Boolean type, and the numerical databases are more widely used [10][11][12]. In such a database, it is also necessary to update the rules, previous scholars have proposed to transform the numerical attribute database into Boolean, and conduct association rules mining.…”
Section: Rule Updatingmentioning
confidence: 99%
“…All of these algorithms can make full use of the rules and information of the previous mining and conduct rule updating, which can avoid duplication work and improve work efficiency. However, in most actual production processes, the attribute values of various fields to be mined are not only Boolean type, and the numerical databases are more widely used [10][11][12]. In such a database, it is also necessary to update the rules, previous scholars have proposed to transform the numerical attribute database into Boolean, and conduct association rules mining.…”
Section: Rule Updatingmentioning
confidence: 99%
“…Numerical comparisons show that the proposed algorithm yields a better approximation of desired filter although a long time is required as compared to some traditional design approaches like frequency transformation, frequency sampling and window method, Semi-definite or cone programming. In comparison to other evolutionary approaches like GA (Boudjelaba et al 2014) or PSO, the proposed AABC has the following advantages:…”
Section: Introductionmentioning
confidence: 97%
“…Most of these algorithms do not have accurate control on pass-band and stop-band regions and also produces sub-optimal impulse response of 2D filters. Recently, evolutionary algorithms have become the most effective alternative to design optimal 2D filters (Boudjelaba et al 2014;Tzeng 2007). It is observed that the recently reported adaptive Genetic Algorithm (GA), by Boudjelaba et al (2014), cannot be used effectively for the design of higher order filters because it leads to sub-optimal solution and also it requires a large computational time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to organisms, the vaccine can prevent pathogenic organisms in advance through analysis of the pathogenic mechanism. The problem-solving process requires some prior knowledge of the evolution environment and the estimation of the best individual gene, as stated in [10][11][12].…”
Section: Algorithm Analysismentioning
confidence: 99%